Liposomal Bupivacaine and Ropivacaine Adductor Canal Blocks for Anterior Cruciate Ligament Reconstruction Provide Similar Postoperative Analgesia - DeMaio, Emily L.; Hunnicutt, Jennifer L.; Haley, Rebecca M.; Nazzal, Ehab; Chen, Yunyun; Premkumar, Ajay; Lamplot, Joseph D.; Samady, Heather A.; Gottschalk, Michael B.; Xerogeanes, John W. (The Journal of Knee Surgery, 2022)
The purpose of this study was to compare postoperative pain following anterior cruciate ligament (ACL) reconstruction (ACLR) in patients receiving an adductor canal block (ACB) with ropivacaine (R-ACB) or liposomal bupivacaine (LB-ACB). The secondary purpose was to compare opioid consumption. A prospective cohort study of patients undergoing ACLR at an academic medical center was conducted from November 1, 2018 to November 21, 2019. The first cohort received R-ACB and 30 tablets of 5/325 mg oxycodone/acetaminophen. After June 13, 2019, the second cohort received LB-ACB and 20 tablets of 5/325 mg oxycodone/acetaminophen with the reduction in opioids prescribed resulting from a hospital quality improvement initiative to decrease narcotic consumption. From postoperative days 0 through 6, pain was assessed thrice daily using a numeric rating scale. Total postoperative opioid consumption was reported via tablet count and converted to oral morphine equivalents (OMEs). During this period, 165 subjects underwent ACLR, and 126 met the eligibility criteria (44.4% female, 55.6% male; mean ± standard deviation: 28.7 ± 13.7 years). Sixty-six (52.4%) received LB-ACB, and 60 (47.6%) received R-ACB (p = 0.53). The most common graft utilized was quadriceps autograft (63.6% LB-ACB; 58.3% R-ACB, p = 0.76). Mean postoperative pain scores were similar between groups during the entire postoperative period (p ≥ 0.08 for POD 0–6). While postoperative opioid consumption was lower among patients receiving LB-ACB (median OME [interquartile range]: 28.6 [7.5–63.8] vs. 45.0 [15.0–75.0], p = 0.023), this only amounted to an average of 2.2 tablets. Patients receiving LB-ACB in the setting of ACLR reported similar postoperative pain compared with those receiving R-ACB. Despite the second aim of our study, we cannot make conclusions about the effect of each block on opioid consumption given that each cohort received different numbers of opioid tablets due to institutional pressure to reduce opioid prescribing. As few patients completed their opioid prescriptions or requested refills, further reduction in prescription size is warranted. Future studies are necessary to further elucidate the effect of LB-ACB versus R-ACB on postoperative pain and opioid consumption after ACLR.
Keywords: anterior cruciate ligament reconstruction; adductor canal block; liposomal bupivacaine; pain; opioids